2021
DOI: 10.1128/mbio.02861-20
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis TmeA Directly Activates N-WASP To Promote Actin Polymerization and Functions Synergistically with TarP during Invasion

Abstract: Chlamydia trachomatis is a medically significant human pathogen and is an epithelial-tropic obligate intracellular parasite. Invasion of nonprofessional phagocytes represents a crucial step in the infection process and has likely promoted the evolution of a redundant mechanism and routes of entry. Like many other viral and invasive bacterial pathogens, manipulation of the host cell cytoskeleton represents a focal point in Chlamydia entry. The advent of genetic techniques in C. trachomatis, such as creation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 70 publications
(117 reference statements)
3
38
0
Order By: Relevance
“…early effector TmeA. Similar to Tarp, TmeA is important for host cell invasion by directing cytoskeleton changes via altered Arp2/3 dynamics ( McKuen et al, 2017 ; Faris et al, 2020 ; Keb et al, 2021 ). Expression of TmeA in flies via the ubi-GAL4 driver was validated by Western blot ( Figure S3A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…early effector TmeA. Similar to Tarp, TmeA is important for host cell invasion by directing cytoskeleton changes via altered Arp2/3 dynamics ( McKuen et al, 2017 ; Faris et al, 2020 ; Keb et al, 2021 ). Expression of TmeA in flies via the ubi-GAL4 driver was validated by Western blot ( Figure S3A ).…”
Section: Resultsmentioning
confidence: 99%
“…The validation of Tarp’s bundling activity in vivo and its ability to compete with endogenous host bundlers during F-actin bundle formation adds to the repertoire of molecular functions that Tarp can deploy during Chlamydia infection. Promoting F-actin polymerization at the site of entry is a major Chlamydia strategy during host cell invasion ( Jewett et al, 2006 ; McKuen et al, 2017 ; Ghosh et al, 2020 ; Keb et al, 2021 ) but F-actin bundling itself has yet to be mechanistically implicated. Our finding raises the possibility that F-actin bundling and/or competition with host bundlers is a component of Tarp function in promoting Chlamydia infection.…”
Section: Discussionmentioning
confidence: 99%
“…Arp2/3 recruitment dynamics at entry sites displays dependence on TmeA and TarP One explanation for impaired actin kinetics following TarP and TmeA deletion is that loss of either effector prevents optimal recruitment of the actin nucleator Arp2/3. Indeed, a recent study suggested that the respective signal transduction capabilities of TarP and TmeA form a functional collaboration that enhances recruitment of Arp2/3 and increases the rate of actin polymerization [23,24]. As such, we monitored the recruitment of fluorescent Arp3 at the entry sites of wild-type, cis-complemented, or effector deletion strains in order to assess the contribution of effector collaboration on Arp2/3 recruitment during invasion (Fig.…”
Section: Table 1: Pairwise Correlation Analyses Of Actin Kinetics Following Deletion or Cis-complementation Of Tarp And Tmeamentioning
confidence: 99%
“…Arp2/3 is a complex of proteins which, upon activation, enhances the rate of actin polymerization by nucleating branched actin filaments along a pre-existing “mother” filament (Bailly et al, 1999; Mullins et al, 1998), and the resulting branched network in turn increases the number of sites for Arp2/3 binding and branched nucleation (Higgs and Pollard, 1999). TarP and TmeA activate the Arp2/3 complex via downstream activation of the nucleation promoting factors WAVE2 and N-WASP, respectively (Carabeo et al, 2007; Faris et al, 2020; Keb et al, 2021; Lane et al, 2008). Both nucleation promoting factors have each been shown to be important for Chlamydia engulfment, as targeted disruption of either protein attenuated pathogen uptake (Carabeo et al, 2007; Faris et al, 2020; Keb et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation